Effect of dietary nitrate supplementation on swimming time-trial performance and neuromuscular function - Esen, O. (Manchester Metropolitan University, 2022)
Nitrate (NO3-) supplementation and its ergogenic effects has received considerable interest in the last two decades. Recent evidence has suggested that the potential effects of NO3- supplementation are more evident under hypoxic conditions and activities. The aims of this thesis were to investigate the ergogenic effect of NO3- supplementation on swimming time-trial performances in trained swimmers and to provide novel insight into its potential effects on motor unit activities during brief isometric muscle contractions, a sustained ischemic muscle contraction and recovery in recreationally active people. The specific objectives of this thesis were to (1) undertake a systematic review and meta-analysis of the randomised control trials (RCTs) on inorganic NO3- supplementation and quantify its effect on muscle contractility in healthy adults; (2) investigate the effects of NO3- supplementation on swimming time-trial performances in trained swimmers; and (3) investigate the effects of short-term NO3- supplementation on neuromuscular functions (e.g., motor unit [MU] potential [MUP] size, firing rates [MUFR] and stability of neuromuscular transmission [jiggle]), during brief isometric contractions and sustained ischemic contraction, and after brief recovery in healthy active adults. The participants underwent various supplementation regimens, invasive and non-invasive physiological measurements, and numerous exercise tests to assess the influence of NO3- supplementation on enhancing performance, attenuating fatigue and improving recovery. Chapter 3 showed that NO3- supplementation may have potential to enhance muscle contractility during a short-duration high-intensity dynamic exercise. Chapter 4 demonstrated that NO3- supplementation elevated plasma NO2- concentration and lowered BP but did not enhance short- (100-m) or middle-distance (200-m) swimming performance in moderately-trained swimmers. Chapter 5 illustrated that NO3- supplementation resulted in shorter MUP duration, but had no effect on MUP area, MUFR and near fibre (NF) jiggle, during brief isometric contractions and a sustained contraction with BFR. Likewise, Chapter 6 showed that NO3- supplementation provided shorter MUP duration but had no effect on other MU properties (MUP area, MUFR and II NF jiggle) after brief recoveries with and without BFR following a sustained ischemic contraction. Chapter 5 also reported lowered BP at rest and during muscle contraction in response to increased plasma NO2- concentration. In conclusion, the work presented in this thesis indicates that NO3- supplementation may have potential to enhance power output during short duration (< 10 s) dynamic exercise but has no ergogenic effect on swimming performance during short- and middle-distance activities in moderately-trained swimmers. NO3- supplementation may also influence the some of the properties of a MU population, such as lowering MUP duration during isometric submaximal muscle contractions. Lastly, NO3- supplementation may confer benefits in reducing blood pressure in healthy, active, young adults. Therefore, NO3- supplementation might be considered as an ergogenic aid for exercise where rapid, short, and explosive movements are performed while it also can be recommended as a means for improving cardiovascular health.